Solar electricity (Chichester : John Wiley & Sons, 2000)
This book is divided into seven parts: Electricity from the Sun; Solar Radiation; Solar Cells; Photovoltaic System Engineering; Applications; Environmental Impacts of Photovoltaics; and Advanced and Specialised Topics.
Keywords: Photovoltaic power systems; Photovoltaic power systems; Photovoltaic power generation; Solar cells